TINGKAT KECUKUPAN VITAMIN A, SENG DAN ZAT BESI SERTA FREKUENSI INFEKSI PADA BALITA STUNTING DAN NON STUNTING[Adequacy Levels of Vitamin A, Zinc, Iron, and Frequency of Infections among Stunting and Non Stunting Children Under Five] - Nabilla Siti Hawa Fatimah; Bambang Wirjatmadi (Universitas Airlangga, 2018)
Stunting is a disturbance in linear growth. Defi ciency of micronutrients such as vitamin A, zinc, and iron may disturb secretion of growth hormone. Infection may improve Tumor Necrosis Factor Alpha (TNF-α) and Interleukin 1 (IL-1) that pressing secretion of growth hormone. The purpose of this study is to determine difference adequacy levels of vitamin A, zinc, iron and frequency infection in stunting and non stunting children under fi ve at Puskesmas Bulak Banteng Surabaya. The study was conducted from January to may 2017 with cross sectional design. Thirty-eight children (19 stunting and 19 non stunting) were selected from random sampling. Mann Whitney test was conducted to analyze the differences between variabel in stunting and non stunting. Variable that were signifi cantly different between two groups were vitamin A (p=0.002), zinc (p=0.003) and iron adequacy level (p=0.030). There were no signifi cant differences in frequency of diarrhea and acute respiratory infection among both groups. Vitamin A, zinc, and iron intake should be fullfi lled in order to prevent stunting.